KESIAPAN UJI KOMPETENSI PROGRAM OTOMOTIF DI LEMBAGA KURSUS DAN PELATIHAN (LKP) YOGYAKARTA - Samsul Hadi (Jurnal Taman Vokasi, 2013)
This study aimed to evaluate the readiness of the competency-tests in course and training institutes for automotive programs in Yogyakarta in terms of (1) the institutes’ support, (2) the readiness of the infrastructure and facilities, (3) readiness of the curriculum documents, (4) the learning of plann, (5) the implementation of learn, (6) the learning assessment, and (7) the achievement of the competency-tests. This study was an evaluation study using quantitative approach. The evaluation model was the CIPP (context, input, process, product) by Stufflebeam. The study population consisted of institutes managers, instructures and students at the two course and training institute for automotive programs in Yogyakarta registered and having Nomor Induk Lembaga Kursus (NILEK). The data were analyzed using the descriptive statistic analysis techniques with the SPSS 17 program. The results of the study show that (1) the institutes’ support is in a middle category, (2) the readiness of the infrastructure and facilities is in high category, (3) readiness of the curriculum documents is in a high category; (4) the learning of planis in a high category, (5) the implementation of learn is in a high category, (6) the learning assessment is in a high category, and (7) the achievement of the competency-test is in a middle category.